The effects of pre‐dialysis blood pressure targets on prognosis and health‐related quality of life in haemodialysis patients. Issue 7 (1st April 2021) - Huang, Ying; Jia, Mengting; Li, Shenghong; Lu, Guoyuan; Shen, Yanping
Abstract: Objective: The aim of the study is to investigate the effects of pre‐dialysis blood pressure targets on health‐related quality of life and prognosis and to determine the optimal target for pre‐dialysis blood pressure in haemodialysis patients. Methods: A total of 58 haemodialysis patients undergoing dialysis for more than 3 months were enrolled in the study from 1 January 2018 to 31 December 2018. The subjects were divided into two groups according to their pre‐dialysis blood pressure: a standard target group (pre‐dialysis systolic blood pressure of 110‐140 mm Hg) and a relaxed target group (pre‐dialysis systolic blood pressure of 155‐165 mm Hg). The Quality Metrics SF‐36 survey instrument was used to assess health‐related quality of life in the study participants. In addition, general clinical data and biochemical indicators including heart rate, respiration rate, blood pressure and ultrafiltration volume and rate during dialysis were observed and recorded. Patients were followed‐up for 12 months, and prognostic data were recorded. Death was regarded as the endpoint. Results: Scores on the SF‐36 in the standard target group were significantly higher than those in the relaxed target group, with the exception of the role‐emotional (RE) and mental health (MH) dimensions. At the end of the study, the number of mortality events in the relaxed target group was higher than in the standard target group. There were no other significant differences between the two groups. Conclusion: The scores from the health‐related quality of life survey were higher in standard target group, but no differences in mortality risk between the two groups were observed.